2000
DOI: 10.1002/1097-0142(20000815)89:4<715::aid-cncr1>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of latent membrane protein 1 and matrix metalloproteinase 9 with metastasis in nasopharyngeal carcinoma

Abstract: BACKGROUND Nasopharyngeal carcinoma (NPC) is a highly metastatic carcinoma whose consistent association with Epstein–Barr virus (EBV) has been established. Latent membrane protein 1 (LMP1), an EBV membrane protein expressed in latent infection, is considered to be the EBV oncoprotein. Matrix metalloproteinase 9 (MMP9), one of the MMP families, degrades Type IV collagen, a major component of extracellular matrix and is believed to be crucial for cancer invasion and metastasis. Although MMP9 is reported to be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 33 publications
(30 reference statements)
7
91
0
3
Order By: Relevance
“…Due to lack of data, however, nine articles had to be excluded from the current metaanalysis. The remaining 5 publications with a total of 238 patients 7,9,[17][18][19] demonstrated MMP-9 expression in 150 tissue specimens. The common odds ratio is summarized in Table 2.…”
Section: Results For Mmp-9mentioning
confidence: 99%
See 3 more Smart Citations
“…Due to lack of data, however, nine articles had to be excluded from the current metaanalysis. The remaining 5 publications with a total of 238 patients 7,9,[17][18][19] demonstrated MMP-9 expression in 150 tissue specimens. The common odds ratio is summarized in Table 2.…”
Section: Results For Mmp-9mentioning
confidence: 99%
“…cN status and pN status were considered in two publications, 7,17 whereas one publication considered only pN status, 18 and two other publications 9,19 did not provide any information about lymph node status. None of the studies mentioned compared levels of MMP-expression with cN status or pN status.…”
Section: Results For Mmp-9mentioning
confidence: 99%
See 2 more Smart Citations
“…However, no direct evidence that the R-S cells infected by EBV express TIMP-1 in vitro has been demonstrated. Recently, it has been shown that EBVencoded latent membrane protein-1 (LMP-1) can upregulate MMP-1, 36 or MMP-9 by activating the NF-kB signaling pathway, 37,38 but downregulate reversion-inducing-cysteine-rich protein with Kazal TIMP-1 expression in diffuse large B-cell lymphoma J-W Choi et al motifs (RECK) via the activation of ERK/Sp1 signaling pathway. 39 The RECK encodes a GPI-anchored glycoprotein harboring three protease inhibitor-like domains.…”
Section: Discussionmentioning
confidence: 99%